Hepatitis C Treatment at a Rural Navajo Health Clinic Using Project ECHO - Anna R Nance; Lori S Saiki; Elizabeth G Kuchler; Conni DeBlieck; Susan Forster-Cox (Rural Nurse Organization; Binghamton University, 2020)
Purpose: Hepatitis C incidence is higher among American Indian/Alaskan Native populations than any other racial or ethnic group in the United States. Chronic Hepatitis C complications include cirrhosis of the liver, end stage liver disease, and hepatocellular cancer. Direct acting antiviral treatment taken orally results in > 90% cure, yet rural primary care providers lack the training and confidence to treat and monitor patients with chronic Hepatitis C. Rural patients are reluctant to travel to urban areas for Hepatitis C treatment. Project ECHO is an innovative tele-mentoring program where specialists mentor primary care providers via videoconferencing to treat diseases they would otherwise be unable to manage. The purpose of this quality improvement project was to increase Hepatitis C treatment at a rural Navajo health clinic through partnership with Project ECHO specialists. Methods: This quality improvement project was guided by Lippitt's Phases of Change Theory. The systematic process plan included a protocol for roles and expectations of all members of the healthcare team, a documentation and communication plan, and a tracking system for monitoring patient progress through the plan of care. Outcomes were analyzed by descriptive statistics. Findings: Following partnership with Project ECHO, six patients (31.6%) consented to receiving Hepatitis C treatment at the rural Navajo health clinic. All six were contacted by outreach staff at multiple points during the project. Five (26.3%) completed the full course of drug therapy. Four (21.1%) completed follow-up lab work, of which three (15.8%) had a documented cure by sustained virologic response. Conclusions: Hepatitis C care via Project ECHO-rural clinic partnership was affordable, feasible and not excessively time consuming for a facility with substantial patient outreach resources. Key words: Rural health clinic, Hepatitis C, Project ECHO, tele-mentoring, Native American